Paired C-type lectin receptors mediate specific recognition of divergent oomycete pathogens in C. elegans - Kenneth Liu; Manish Grover; Franziska Trusch; Christina Vagena-Pantoula; Domenica Ippolito; Michalis Barkoulas (Cell Reports, 2024)
Summary: Innate immune responses can be triggered upon detection of pathogen- or damage-associated molecular patterns by host receptors that are often present on the surface of immune cells. While invertebrates like Caenorhabditis elegans lack professional immune cells, they still mount pathogen-specific responses. However, the identity of host receptors in the nematode remains poorly understood. Here, we show that C-type lectin receptors mediate species-specific recognition of divergent oomycetes in C. elegans. A CLEC-27/CLEC-35 pair is essential for recognition of the oomycete Myzocytiopsis humicola, while a CLEC-26/CLEC-36 pair is required for detection of Haptoglossa zoospora. Both clec pairs are transcriptionally regulated through a shared promoter by the conserved PRD-like homeodomain transcription factor CEH-37/OTX2 and act in sensory neurons and the anterior intestine to trigger a protective immune response in the epidermis. This system enables redundant tissue sensing of oomycete threats through canonical CLEC receptors and host defense via cross-tissue communication.